Progressive choreodystonia in X‐linked hyper‐IgM immunodeficiency: a rare but recurrent presentation. Issue 4 (10th March 2022) - Škorvánek, Matej; Jech, Robert; Winkelmann, Juliane; Zech, Michael
Abstract: An association between movement disorders and immune‐system dysfunction has been described in the context of rare genetic diseases such as ataxia telangiectasia as well as infectious encephalopathies. We encountered a male patient who presented immunodeficiency of unknown etiology since childhood. A medication‐refractory, progressive choreodystonic movement disorder emerged at the age of 42 years and prompted an exome‐wide molecular testing approach. This revealed a pathogenic hemizygous variant in CD40LG, the gene implicated in X‐linked hyper‐IgM syndrome. Only two prior reports have specifically suggested a causal relationship between CD40LG mutations and involuntary hyperkinetic movements. Our findings thus confirm the existence of a particular CD40LG ‐related condition, combining features of compromised immunity with neurodegenerative movement abnormalities. Establishing the diagnosis is crucial because of potential life‐threatening immunological complications.